Desain Energy Storage System Untuk Terminal Charging Kendaraan Listrik Berdasarkan Intensitas Cahaya Matahari Sepanjang Hari - Ridho Anggu Frasasti; Parlin Siagian; Hermansyah Alam (Jurnal Serambi Engineering, 2024)
Utilization of new, renewable energy (EBT) resources is the most important field in developing countries like Indonesia. The development of effective methods for evaluating alternative energy sources in the automotive industry has always been a need for cost-effective design analysis and one of the viable energy sources is electrical energy. Electric Vehicles (EV) are the application of photovoltaic energy using a combination of a charge controller based on a battery charging strategy with a unidirectional PWM technique based on a grid to vehicle strategy in the Smart Grid. Energy supplies in the world are currently decreasing, especially the energy used to generate electricity. With the widespread use of electric vehicles (EVs), it is important to plan charging by considering the behavior of EV drivers and demand on the electricity grid. Because the average solar insolation value in Indonesia is quite high, this can minimize dependence on the electricity grid and maximize the use of solar energy for energy storage systems for electric vehicles.